PREDISPOSING FACTORS FOR PUERPERAL ENDOMETRITIS - Eduarda Almeida de Souza, Cicera; da Silva Araújo, Cíntia; Mohamad Abdel Salam Suleiman, Nariman; Ohanny Virgílio de Carvalho, Nicolly; Barbosa Resende, Danilo; Vieira Benevides Ferreira, Arthemis; Afonso de Carvalho, Thiozano; Carla Campos Coêlho, Laise (Health and Society, 2022)
Objectives: To show how to prevent puerperal endometritis. Methodology: This is an integrative literature review with a descriptive and exploratory approach, carried out from October 2022 to December 2022 based on a bibliographic survey in the scientific databases of virtual health libraries: Latin American Literature and Caribbean Health Sciences (LILACS), Nursing Database (BDENF) and International Health Sciences Literature (MEDLINE). Thus, a thorough reading of the titles and abstracts was carried out, highlighting 15 studies, and after reading them in full, 7 articles were chosen to compose the final sample. Results and Discussion: From the analysis of the literature, it was evidenced that cesarean delivery is the main factor for triggering puerperal infections and that, through all the pre-existing risk factors, preventive measures must be adopted by the entire team multidisciplinary approach, antiseptic techniques must be performed correctly, adherence to humanized childbirth is paramount and must be advocated as an essential factor, hand washing, ongoing education for the health team, use of sterile materials and the use of Individual Protection are forms of prevention that will minimize the risks of Puerperal Infections in all their pre-delivery, intraoperative and postoperative phases. Final Considerations: The study showed that the nursing professional can provide important assistance for the prevention of Puerperal Infections, and that the multidisciplinary and interdisciplinary team of collaborators must act systematically in the process of reporting any adverse event. And that a set of actions performed correctly and effectively can prevent cases of Puerperal Infections.